Near-Surface Geochemical Anomalies Integrated with Seismic and Well Data over the Contact of the Outer Carpathians and the Carpathian Foredeep (SE Poland) - Henryk Sechman; Adrianna Góra; Anna Twaróg; Piotr Guzy; Ewelina Górska-Mruk; Wojciech Górecki (Geofluids)
The objective of this study is to interpret the regularities in distribution of surface geochemical anomalies observed in a fragment of the contact zone between the Carpathian Fold-and-Thrust Belt and the Carpathian Foredeep (SE Poland). The surface geochemical survey included a total of 670 soil gas samples analyzed by gas chromatography, integrated with seismic cross sections, and supplemented by production data from wells. Maximum concentrations of methane, total alkanes C2-C5, total alkenes C2-C4, H2, and CO2 measured in soil gas samples were 27.1 vol.%, 45.3 ppm, 0.49 ppm, 0.232 vol.%, and 6.29 vol.%, respectively. Traces of alkanes detected in samples are the result of microseepage from a few accumulations of various compositions. Methane and ethane migrate primarily from relative shallow Miocene strata, and higher alkanes from deeper Miocene strata and from Paleozoic-Mesozoic basement. We found relatively high positive correlation between the distribution of surface geochemical anomalies and the relative intensity of hydrocarbon shows recorded in the wells. The location and range of 13 anomalous zones are controlled by the patterns of both the Dębno and the Wojnicz slice-folds. Most of the anomalies occur over the Wojnicz Trough, suggesting the presence of conventional accumulations and/or the sites where the Miocene mudstone and heterolithic formations are saturated with gas.